Microbial nanotechnology : advances in agriculture, industry and health sectors - Ahmad, Razi; Bhardwaj, Neha; Bhardwaj, Sanjeev; Chauhan, Sonu; Chopra, Monika; Datta, Vasudha; Dhoni, Supriya; Fiodor, Angelika; Gianni, Eleni; Gulati, Alka; Gulati, Sachin; Jundal Majid, Mohammed; et al. (De Gruyter, 2022)
"Applications of microbial nanotechnology are currently emerging with new areas being explored. Biosynthesis of nanomaterials by microorganisms is a recently attracting interest as a new, exciting approach towards the development of 'greener' nanomanufacturing compared to traditional chemical and physical approaches. This book will cover recent advances of microbial nanotechnology in agriculture, industry, and health sectors."--